Cytoplasmic Tail of MT1-MMP: A Hub of MT1-MMP Regulation and Function - Strouhalova, Katerina; Tolde, Ondřej; Rosel, Daniel; Brábek, Jan (International journal of molecular sciences, 2023)
MT1-MMP (MMP-14) is a multifunctional protease that regulates ECM degradation, activation of other proteases, and a variety of cellular processes, including migration and viability in physiological and pathological contexts. Both the localization and signal transduction capabilities of MT1-MMP are dependent on its cytoplasmic domain that constitutes the final 20 C-terminal amino acids, while the rest of the protease is extracellular. In this review, we summarize the ways in which the cytoplasmic tail is involved in regulating and enacting the functions of MT1-MMP. We also provide an overview of known interactors of the MT1-MMP cytoplasmic tail and the functional significance of these interactions, as well as further insight into the mechanisms of cellular adhesion and invasion that are regulated by the cytoplasmic tail.
Keywords: post-translational modifications; signální transdukce; MT1-MMP; intracellular trafficking; Matrix Metalloproteinase 14; Signal Transduction; matrix metalloproteinases; Cell Adhesion; cell invasion; Cell Movement; buněčná adheze; matrixová metaloproteinasa 14; pohyb buněk